Novel Coronavirus Outbreak and Career Development: A Narrative Approach Into the Meaning for Italian University Graduates - Parola, Anna (Frontiers in Psychology, 2020)
Introduction. In times of economic crisis, the literature showed that young people have always been the high-risk category. The COVID-19 outbreak and the consequence on the economic level have increased the sense of uncertainty and precariousness experienced by young people. The current scenario has forced young people in the school-to-work transition points to re-think their career plans. Although already the difficulties of school-to-work transition lead to distress and mental health problems in young people, the slowdowns imposed by the Coronavirus could add up to these difficulties. The present study aimed to explore the processes of career development and career planning in the Coronavirus era. 20 Italian university graduates have been involved. Methods. A quantitative measure was used to evaluate the affective (positive/negative) experience. A narrative prompt was used to understand the individual dimensions of career planning. Cluster analysis was carried out by an unsupervised ascendant hierarchical method to explore the themes of the narrations. Results. Italian young adults have tended to experience negative affect in recent weeks of quarantine. The themes highlight in the narratives showed that Italian young adults experience feelings of fear, uncertainty, anxiety about the post-pandemic future. Conclusions. The results appear as a starting point to re-think possible interventions for this group post-lockdown and post-pandemic.